Broken Home pada Remaja dan Peran Konselor - Sabilla Hasanah; Elvi Sahara; Indah Permata Sari; Sri Wulandari; Kamil Pardumoan (JRTI (Jurnal Riset Tindakan Indonesia), 2017)
Families are encouraged by Broken Home circumstances marked by parental divorce, or those who have single parents (Single Parent). At times such as the attention and affection of the parents make the child.Jika already stepped on the teenager can cause a crisis that is usually characterized by the tendency of deviant behavior or mischief. Negative reactions caused by adolescents that can damage the physical and personality. This requires the assistance of teachers Guidance and Counseling to develop Guidance and Counseling services in eradicating students' problems as a result of Broken Home.